Kathryn A. Kleppinger. Branding the 'Beur' Author: Minority Writing and the Media in France, 1983-2013. Liverpool: Liverpool UP, 2015. - Christopher Ice (Studies in 20th & 21st Century Literature, 2018)
Review of Kathryn A. Kleppinger. Branding the 'Beur' Author: Minority Writing and the Media in France, 1983-2013. Liverpool: Liverpool UP, 2015. xi + 271 pp.
Keywords: Francophone Literature; Maghrebi Diaspora; Immigrant Communities in France; Minority Representation; Media Studies